Wien - Geschichte einer Stadt Band 3: Von 1790 bis zur Gegenwart - Opll, Ferdinand (2006)
This volume is the last and final part of a trilogy on a detailed history of Vienna. It covers the period from 1790 until the present times. For the decisive forces as well as the inhabitants of the city this era of the urban development of Vienna has to be counted among the most dramatic periods characterised by a great number of real breaks in history. Napoleonic occupation, the revolution of 1848, the constitutional as well as the economic and social changes from the middle of the 19th century onwards, the final end of the position as "Reichshaupt- und Residenzstadt" (capital and residential city of the Austro-Hungarian empire) at the end of World War I, the challenging and complicated inter-war-period, Vienna's fate under Nazi-domination, the air raid of World War II and its end as well as the years after 1945 so far never described in such a comprehensive manner - all these events establish the chronological screen for the description and mark decisive incidents being treated here. In a chronological framework six authors arrange a pattern of Vienna's political, social, economic and cultural history. An innovative step is marked by the attempt to give a description of the ever so decisive periods like the "Fin-de-Siècle" and the complicated years after 1918 considering the intellectual mainstream and including men of letters and their works as contemporary witnesses and references. Vienna's development after 1945 - regarding the political history until the elections of 2001, the social and economic history in some aspects even furthermore - has not been treated in such a profound manner so far. This volume - as its predecessors - imparts the latest state of research to a wide public, supported by many illustrations and a large bibliography as well as a useful register of place names and persons.